GEOLOGICAL AND GEOPHYSICAL STUDIES OF MUKAH COALFIELD AREA, SARAWAK, MALAYSIA - MOHD ROSDI, NADHIRAH (2019)
Tertiary coal seams in Mukah Coalfield are discontinuous laterally in terms of depth and thickness of the seams.